Investigation of drone implementation for commercial use in Thailand - Pathomporn Ruenklin; Endress, Tobias; Badir, Yuosre F. M.; Junaid, Muhammad; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2024)
Safety and security are one of the primary concerns with commercial drones, ensuring their safe operation. Drones can pose risks to people and property if they malfunction, collide with other objects, or fall from the sky. In Thailand, there has been a significant increase in the commercial use of UAS recently. Ongoing research and development efforts are focused on developing and implementing advanced CNS technologies specifically tailored for drones. These include communication protocols, navigation systems, and surveillance solutions that can enable safe and efficient drone operations in various scenarios. Security agencies such as the military and police in Thailand are not yet well equipped to effectively regulate the commercial use of UAS to secure lives and property for local citizens. This study investigates the application of commercial unmanned aerial vehicles in Thailand. The researcher compiled the literature and relevant research papers and used them as supporting information to increase credibility. A qualitative method incorporates secondary data analysis, and an interview approach is employed as primary data. The researcher uses a purposive sampling technique by interviewing the relevant parties and gathering information from various documents for analysis. A study of UAV utilization for Agriculture in Thailand shows that Thailand's Agriculture section is one of the economy's largest sectors and is growing dramatically. No national unmanned aerial vehicle standard or certification exists, whether fully imported or domestically assembled because no standard exists to support it. Relevant organizations should be prepared to set standards for UAVs in Thailand by considering joining ISO TC/20 UAS to discuss, exchange, and determine facts on the use of UAVs in the country. Therefore, agencies should be integrated to be involved in unmanned aerial work.
An Internship Report submitted in partial fulfillment of the requirements for the degree of Master of Science in Business Analytics and Digital Transformation
Internship Report (M. Sc.) - Asian Institute of Technology, 2024
Keywords: Drone aircraft -- Thailand; Aeronautics, Commercial -- Thailand; Drone aircraft -- Industrial applications -- Thailand